Nanocomposite of (α-Mn3O4/MnO)@rGO as a high performance electrode material for supercapacitors. (10th September 2021) - Gangwar, A.; Das, T.; Shaw, S.K.; Prasad, N.K.
Highlights: Nanocomposite (α-Mn3 O4 /MnO)@rGO is synthesized by one step sol-gel route. The obtained optimum CS value was ~237 Fg −1 at a constant current of 1 mA. It exhibited excellent Es (10.8 Wh/kg) and Pd (W/kg) at a constant current of 20 mA. Low Rct and Warburg resistance supported its applicability as SCS electrode material. Abstract: It is demonstrated for the first time, strongly coupled reduced graphene oxide with α-Mn3 O4 /MnO nanocomposite acts as an electrode material for supercapacitors. The material has displayed an optimum specific energy of 21 and 10.8 Wh/kg, and a power density of 206 and 3979 W/kg at the constant current values of 1 and 20 mA respectively. Furthermore, capacity retention of ~92.7 % was observed after 3000 cycles at a scan rate of 100 mV/s. This material was synthesized via a single step sol-gel route and subsequently calcined at 700 °C in an inert atmosphere (N2 ). The obtained (α-Mn3 O4 /MnO)@rGO nanomaterial was characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), high resolution transmission electron microscope (HR-TEM), scanning tunneling electron microscope-energy dispersive x-ray spectroscopy (STEM–EDS) to investigate the phase and structural morphology. Furthermore, electrochemical studies such as cyclic voltammetry (CV), Galvanostatic charge–discharge (GCD), and electrochemical impedance spectroscopy for the nanocomposite were performed with three electrode systems in an aqueous electrolyte of 1 M KOH.